FORMATION OF OPTIONS FOR DELIVERY OF GOODS IN THE ENVIRONMENT OF THE PROJECT OF THE ORGANIZATION OF SEA TRANSPORTATIONS - Павлова, Наталья (SWorldJournal, 2020)
The article discusses the methodological provisions for the formation of options for the delivery of goods when organizing sea transportation using the methodology of project management. The tasks of constructing the routes of ships in the operational man